MANAGING AND SHARING RESEARCH DATA : A Guide to Good Practice - Corti, Louise, author 561099; Eynden, Veerle van den, author 627933; Bishop, Libby, author 627934; Woollard, Matthew, author 627935 (Thousand Oaks, California : SAGE Publications, 2020)
Includes bibliographical references and index